2016
DOI: 10.1016/j.ygyno.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-induced peripheral neuropathy: Current status and progress

Abstract: As there are increasing numbers of cancer survivors, more attention is being paid to the long term unwanted effects patients may experience as a result of their treatment and the impact these side effects can have on their quality of life. Chemotherapy-induced peripheral neuropathy (CIPN) is one of the most common long-term toxicities from chemotherapy. In this review we will briefly review the clinical presentation, evaluation and management of chemotherapy-induced peripheral neuropathy, with a focus on CIPN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
208
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(222 citation statements)
references
References 69 publications
6
208
0
8
Order By: Relevance
“…Another study showed clinical deterioration in 31% of patients with aggravation of peripheral neuropathy peaking between 2.5 and 5.5 months following discontinuation of cisplatin [18]. As mentioned, CIPN is dose related and develops coincidently with accumulating doses of neurotoxic agents and typically regresses after therapy is terminated with the exception of platinum and vincristine compounds [19,20]. The progression of CIPN after chemotherapy discontinuation was observed in 30% of patients treated with vincristine.…”
Section: Evolutionmentioning
confidence: 95%
See 1 more Smart Citation
“…Another study showed clinical deterioration in 31% of patients with aggravation of peripheral neuropathy peaking between 2.5 and 5.5 months following discontinuation of cisplatin [18]. As mentioned, CIPN is dose related and develops coincidently with accumulating doses of neurotoxic agents and typically regresses after therapy is terminated with the exception of platinum and vincristine compounds [19,20]. The progression of CIPN after chemotherapy discontinuation was observed in 30% of patients treated with vincristine.…”
Section: Evolutionmentioning
confidence: 95%
“…In more severe cases, complete resolution is not possible and mild foot drop, decreased deep tendon reflexes or distal sensory deficits may be the residual signs. Sixty-six % of treated patients find complete recovery [19,24].…”
Section: Evolutionmentioning
confidence: 99%
“…The mechanistic basis of this side effect remains uncertain (4), although prior studies have demonstrated that paclitaxel induces injury to sensory neurons, morphological and biochemical alterations in dorsal root ganglia (DRG) satellite cells, hyperplasia/hypertrophy of macrophages in the peripheral nervous system, and increases microglial and astrocyte activation within the spinal cord (5,6). Paclitaxel also causes an acute pain syndrome that develops within 1-3 days of paclitaxel administration, and that resolves within 1 week.…”
Section: Introductionmentioning
confidence: 99%
“…The predictive strategies have predominantly focused on the search for hereditary biomarkers that could identify patients at increased risk of toxicity through candidate gene or genome-wide association studies (5,11,12). However, the findings from these studies done to date have identified nonoverlapping single or pathway biomarker associations that preclude immediate clinical implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, these drugs all produce treatment-limiting peripheral neuropathy, for which there is no reliable clinical intervention. The primary treatment of CIPN is to reduce the chemotherapy dose and to extend the interval between treatments, or cease treatment completely (3). However, this is not an optimal choice for the long-term prognosis of the patient.…”
Section: Introductionmentioning
confidence: 99%